Impact of opioid law on prescriptions and satisfaction of pediatric burn and orthopedic patients: An epidemiologic study. - Megan Armstrong; Jonathan I Groner; Julie Samora; Vanessa A Olbrecht; Nguyen K Tram; Dana Noffsinger; Edward W Boyer; Henry Xiang (PLoS ONE, 2023)
Objectives The objective of this study was to determine the reduction in prescribed opioid pain dosage units to pediatric patients experiencing acute pain and to assess patient satisfaction with pain control 90-day post discharge following the 2017 Ohio opioid prescribing cap law. Methods The retrospective chart review included 960 pediatric (age 0-18 years) burn injury and knee arthroscopy patients treated between August 1, 2015-August 31, 2019. Prospectively, legal guardians completed a survey for a convenience sample of 50 patients. Opioid medications (days and morphine milligram equivalents (MMEs)/kg) prescribed at discharge before and after the Ohio law implementation were collected. Guardians reported experience and satisfaction with their child's opioid prescription at 90-days post discharge. Results From pre-law to post-law, there was a significant decrease (p<0.001) within the burn and knee cohorts in the median days (1.7 to 1.0 and 5.0 to 3.8, respectively) and median total MMEs prescribed (15.0 to 2.5 and 150.0 to 90.0, respectively). An interrupted time series analysis revealed a statistically significant decrease in MMEs/kg and days prescribed at discharge when the 2017 Ohio opioid prescription law went into effect, with an abrupt level change. Prospectively, more than half of participants were satisfied (72% burn and 68% knee) with their pain control and felt they received the right amount of medication (84% burn and 56% knee). Inpatient opioid use was not changed pre- and post-law. Conclusions Discharge opioids prescribed for pediatric burn and knee arthroscopy procedures has decreased from 2015-2019. Caregivers varied greatly in their satisfaction with pain control and the amount of opioid prescribed.